Pengaruh Kualitas Informasi terhadap Keputusan Pembelian Online Tiktok Shop (Sudi Kasus pada Mahasiswa Fakultas Ekonomi Universitas Negeri Gorontalo) - Erlin. S Uge; Hapsawati Taan; Yulinda L. Ismail (IPM2KPE, 2024)
The purpose of this research is to determine the magnitude of the influence of information on Tiktok Shop online purchasing decisions. This type of research is quantitative research which is analyzed using statistics. The population in this study were students from the Faculty of Economics, Gorontalo State University who made online purchases at the TikTok shop. The sampling technique used nonprobability sampling with a purposive sampling method with 97 respondents by distributing questionnaires via Google Form. The data analysis method uses a Simple Linear Regression Test. The research results show that the quality of information (X) has a significant effect on purchasing decisions (Y) with a value of 0.000 < 0.1. The conclusion is that the quality of information has a positive and significant effect on online TikTok shop purchasing decisions among economics faculty students. Keywords: Information Quality, Purchasing Decision